Validation of a Method for Quantitation of Soybean Lectin in Commercial Varieties. (11th July 2015) - Breeze, Matthew L.; Leyva‐Guerrero, Elisa; Yeaman, Grant R.; Dudin, Yelena; Akel, Ryan; Brune, Phil; Claussen, Fred; Dharmasri, Cecil; Golbach, Jenny; Guo, Rong; Maxwell, Carl; Privalle, Laura; et al.
Abstract: Soybean agglutinin (SBA) protein, also known as soybean lectin, is regarded as an anti‐nutrient due to its negative effect on the ability of monogastric animals to gain weight following consumption of raw soybean seed. Historically, SBA has been measured using a time‐consuming and cumbersome hemagglutination procedure. The objective of our research was to obtain a validated methodology that is precise and accurate in the measurement of SBA while allowing minimally equipped laboratories to effectively conduct the analysis, thus our focus was on evaluating an existing commercially available ELISA, an enzyme‐linked‐lectin‐assay (ELLA), and a hybrid ELISA/ELLA. A new ELLA technique that can detect and quantify lectins was chosen and modified specifically for the quantitation of SBA in soybean seed. The proposed ELLA methodology is similar to a standard sandwich ELISA, and uses polyacrylamide‐linked N ‐acetylgalactosamine (Gal–NAc–PAA) for a capture phase and the biotinylated version (Gal–NAc–PAA–Biotin) for detection. Based upon the validation data, the ELLA method can precisely and accurately determine soybean lectin levels in soybean seed. The validated ELLA method was used to quantify SBA in nine commercial soybean varieties introduced between 1972 and 2008 and demonstrated that the natural variability of SBA is subject to the effects of genotype and environment.